2000
DOI: 10.1007/pl00009766
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tracheid dimensions on variations in maximum density of Picea glehnii and relationships to climatic factors

Abstract: An investigation was made of the effects of tracheid dimensions on variations in the maximum density of Picea glehnii Mast., which were associated with climatic changes. Radial cell diameter and the thickness of the tangential cell walls of the last-formed cells in 90 annual rings of nine trees with different annual ring widths were analyzed by image analysis. Correlations between maximum density and tracheid dimensions indicated that changes in maximum density were due mainly to changes in cell wall thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(53 citation statements)
references
References 25 publications
3
47
1
2
Order By: Relevance
“…2). This finding is consistent with other studies of MXD (e.g., Schweingruber 1988;D'Arrigo et al 1992;Davi et al 2003;Frank and Esper 2005;D'Arrigo et al 2009), and is due to the influence of summer climate on the thickness of the cell wall in the latewood of the annual ring (Yasue et al 2000). We select for our reconstruction target the mean monthly July and August temperatures from the Goddard Institute for Space Studies (GISS) Surface Temperature Analysis (GISTEMP; Hansen et al 2010) 1200-km grid cell associated with the Firth River site, since it is continuous, long, represents a large-scale regional mean, and can be readily compared to climate (Fig.…”
Section: Methodssupporting
confidence: 93%
“…2). This finding is consistent with other studies of MXD (e.g., Schweingruber 1988;D'Arrigo et al 1992;Davi et al 2003;Frank and Esper 2005;D'Arrigo et al 2009), and is due to the influence of summer climate on the thickness of the cell wall in the latewood of the annual ring (Yasue et al 2000). We select for our reconstruction target the mean monthly July and August temperatures from the Goddard Institute for Space Studies (GISS) Surface Temperature Analysis (GISTEMP; Hansen et al 2010) 1200-km grid cell associated with the Firth River site, since it is continuous, long, represents a large-scale regional mean, and can be readily compared to climate (Fig.…”
Section: Methodssupporting
confidence: 93%
“…We found spring precipitation to be negatively correlated with TRW, possibly by delaying snowmelt and therefore shortening the growing season (Kirdyanov et al, 2003). Adverse effects of increased cloudiness on photosynthetic activity are likely the reason for slightly negative correlations between summer precipitation and MXD (Yasue et al, 2000). Interestingly, relative humidity, which at this high elevation site may be considered as a proxy of overcast conditions, shows an even stronger negative connection with MXD.…”
Section: Precipitation and Relative Humiditymentioning
confidence: 64%
“…Nevertheless, sunshine directly affects wood density and carbon isotopes, and anatomical studies showed that a decrease in light intensity and duration results in a decline in tracheid dimension and lighter latewood (Yasue et al, 2000). Sunshine hours were here identified as the leading climatic factor controlling δ 13 C variability during the recent calibration period.…”
mentioning
confidence: 68%
“…It is plausible that such a reduction could be caused by formation of compression wood on the abaxial side of the branches [1,19]. Compression wood is denser than normal wood [30] and in conifers an increase in wood density is often due to a decrease in tracheid lumen [36]. A decrease in tracheid lumen would also decrease specific conductivity.…”
Section: Spatial Variationmentioning
confidence: 99%